2013
DOI: 10.1158/1940-6207.capr-13-0022
|View full text |Cite
|
Sign up to set email alerts
|

Simple Clinical Risk Score Identifies Patients with Serrated Polyps in Routine Practice

Abstract: Large, proximal, or dysplastic (LPD) serrated polyps (SP) need accurate endoscopic recognition and removal as these might progress to colorectal cancer. Herewith, we examined the risk factors for having 1 LPD SP. We developed and validated a simple SP risk score as a potential tool for improving their detection. We reviewed clinical, endoscopic, and histologic features of serrated polyps in a study of patients undergoing elective colonoscopy (derivation cohort). A self-administered questionnaire was obtained. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…A German study reported an increased risk of HPs in those older than 55 years of age (age >55 vs. ≤55 years: OR 1.72, 95% CI 1.00, 2.96) [42] while a Japanese study reported similar results (age 55-64 vs. ≤44 years: OR 2.06, 95% CI 1.13, 3.78; age ≥65 vs. ≤44 years: OR 2.90, 95% CI 1.60, 5.30) [46] (Table 1). Two studies reported increased risk of SPs among individuals older than 50 years of age: Bouwens et al (Age >50 vs. ≤50 years: OR 2.2, 95% CI 1.3, 3.8) and Burnett-Hartman et al (age 50-59 vs. <50 years: OR 1.87, 95% CI 1.20, 2.91) [48, 51]. …”
Section: Specific Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…A German study reported an increased risk of HPs in those older than 55 years of age (age >55 vs. ≤55 years: OR 1.72, 95% CI 1.00, 2.96) [42] while a Japanese study reported similar results (age 55-64 vs. ≤44 years: OR 2.06, 95% CI 1.13, 3.78; age ≥65 vs. ≤44 years: OR 2.90, 95% CI 1.60, 5.30) [46] (Table 1). Two studies reported increased risk of SPs among individuals older than 50 years of age: Bouwens et al (Age >50 vs. ≤50 years: OR 2.2, 95% CI 1.3, 3.8) and Burnett-Hartman et al (age 50-59 vs. <50 years: OR 1.87, 95% CI 1.20, 2.91) [48, 51]. …”
Section: Specific Risk Factorsmentioning
confidence: 99%
“…Men were found to have an increased risk of SPs by Erhardt et al (OR 1.83, 95% CI 1.05, 3.18), just as women were found to have decreased risk of SPs by Morimoto et al (OR 0.6, 95% CI 0.5, 0.9) [42, 45] (Table 2). However, other studies have not shown any significant association between sex and SPs, including Omata et al (male OR 1.54, 95% CI 0.97, 2.44), Min et al (male OR 1.82, 95% CI 0.99, 3.32), Bouwens (male OR 0.9, 95% CI 0.6, 1.2), Burnett-Hartman (female OR 1.06, 95% CI 0.8, 1.4), and Wallace (female proximal OR 1.07 95% CI 0.82, 1.39) [48, 51, 52, 56]. …”
Section: Specific Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, investigators in The Netherlands developed a risk score to predict the detection of large, proximal, or dysplastic serrated polyps in patients undergoing colonoscopy 25. The derivation cohort consisted of 2,244 patients and 2,402 patients in the validation cohort.…”
Section: Risk Factors Associated With Serrated Lesionsmentioning
confidence: 99%